2020
DOI: 10.3390/s20236819
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Low-Cost Particulate Matter Sensors from the Developers’ Perspectives

Abstract: The concerns related to particulate matter’s health effects alongside the increasing demands from citizens for more participatory, timely, and diffused air quality monitoring actions have resulted in increasing scientific and industrial interest in low-cost particulate matter sensors (LCPMS). In the present paper, we discuss 50 LCPMS models, a number that is particularly meaningful when compared to the much smaller number of models described in other recent reviews on the same topic. After illustrating the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 98 publications
0
65
0
2
Order By: Relevance
“…The authors wish to make the following corrections to this paper [1]: In the original article, the sorting order of the reference list starting from reference no. 110 up to reference no.…”
mentioning
confidence: 99%
“…The authors wish to make the following corrections to this paper [1]: In the original article, the sorting order of the reference list starting from reference no. 110 up to reference no.…”
mentioning
confidence: 99%
“…Wesseling et al (2019) analyzed these stationary sensor measurements and concluded that the rise of citizen science and increasingly better performing low-cost sensors will change the role of Environmental Protection Agencies (EPAs) significantly in the coming years [ 13 ]. In recent years, several studies have given an extensive overview of the use of low-cost sensors, their calibration options and other technical considerations [ 16 , 17 , 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Wesseling et al (2019) analyzed these stationary sensor measurements and concluded that the rise of citizen science and increasingly better performing low-cost sensors will change the role of Environmental Protection Agencies (EPAs) significantly in the coming years [13]. In recent years, several studies have given an extensive overview of the use of low-cost sensors, their calibration options and other technical considerations [16][17][18] Another reason for the increasing interest in low-cost sensors is their potential for personal exposure monitoring [17,19]. Typically, estimates for exposure are based on modeled PM concentrations at home addresses or zip codes.…”
Section: Introductionmentioning
confidence: 99%
“…These detectors have been utilized successfully in dense air quality monitoring networks, although cross-sensitivity between different gases (e.g., O 3 and NO 2 ), influence of relative humidity, temperature dependency and longterm drift may often hinder their overall performance (Jiao et al, 2016;Cross et al, 2017). For particle phased pollutants, the dominant detection technique is based on the detection of light scattered from illuminated particles (Karagulian et al, 2019;Alfano et al, 2020). This technique is applicable mainly for the particle mass concentration monitoring as its sensitivity for the detection of ultrafine particles is limited (Hinds, 1999).…”
Section: Introductionmentioning
confidence: 99%